Zdefiniować fantastykę, czyli „fantastyczne" (i nie tylko) teorie literatury fantastycznej - Niziołek, Małgorzata (Wydawnictwo Naukowe UAM, 2005)
The aim of this paper is to define fantasy through juxtaposing, comparing and sorting existing definitions. Taking into consideration elements of fantasy, such as ambiguity and insecurity, a crack in everyday life and the anxiety of the indefinable, the most controversial issues in fantasy were discussed. In the end, a new pattern of relations between fantasy, fabulousness, sciencefiction, and magic was suggested.
How to define fantasy - fantastic and other theories of fantasy